More risk - less solidarity? An experimental investigation - Jano Costard (European University Viadrina, Department of Business Administration and Economics, 2011)
A solidarity game was conducted where participants were able to choose between two lotteries with same expected values. However, in one lottery, the risky one, participants faced a higher probability to receive no endowment. The winners were then able to discriminate between subjects risk attitude when it came to voluntary transfers from winners to losers in randomly formed three person groups. The results indicated that risk takers were not fully held responsible for their self-inflicted neediness, although they received on average fewer transfers than non-risk-takers. In fact, group favoritism is observed, where non-risk-takers transferred more to loosing non-risk-takers and risk-takers transferred more to loosing risk-takers. This behavioral pattern was stable across different versions of group compounding, profession and gender. Nevertheless, a gender effect was found with regard to lottery choice and the amount of money transferred. Furthermore, similarities can be seen between the results of the experiment and certain aspects of the current financial crisis. Among them borrowing in non-recourse states in the USA, the role of rating agencies and the hiring of failed CEOs. – – Es wurde ein Solidaritätsspiel durchgeführt, in dem die Teilnehmer aus zwei Lotterien mit gleichen Erwartungswerten wählen konnten. Allerdings war die Wahrscheinlichkeit zu verlieren und keinen Gewinn zu erhalten bei der riskanten Lotterie höher. In Dreiergruppen, bestehend aus Gewinnern und Verlierern, hatten die Gewinner die Möglichkeit freiwillig etwas von ihrem Gewinn an die Verlierer abzugeben. Dabei konnten sie zwischen dem Risikoverhalten der Verlierer unterscheiden. Die Ergebnisse offenbaren, dass risikoreiche Verlierer nicht komplett für ihre selbstverschuldete "Armut" verantwortlich gemacht wurden, obwohl sie im Durchschnitt weniger Transfers erhielten als Verlierer die kein Risiko eingegangen sind. Vielmehr ist ein Favorisieren der eigenen Gruppe zu beobachten, wobei "risikolose Gewinner" mehr an "risikolose Verlierer" transferiert haben und "risikoreiche Gewinner" mehr an "risikoreiche Verlierer" transferierten. Dieses Verhaltensmuster ist stabil über verschiedene Gruppenzusammensetzungen, die fachliche Ausrichtung und das Geschlecht der Teilnehmer des Experiments. Im Gegensatz dazu wurde ein geschlechtsspezifischer Effekt bei der Wahl der Lotterie und bei der Höhe der Transfers beobachtet.
http://hdl.handle.net/10419/41396
Keywords: 330; Risikopräferenz; Glücksspiel; Solidarität; Soziale Gruppe; Spieltheorie; Test